Legal status of public control entities over the activities of the National Police in Ukraine - V. A. Doroshenko (Bulletin of Kharkiv National University of Internal Affairs)
The article analyses and clarifies the concept of public control over the activities of the National Police in Ukraine. Public control over the activities of the police is defined as a targeted activity of the organised and unorganised public regarding the quality of police activities and the effectiveness of the tasks and duties assigned to police representatives. The importance of public control over the activities of law enforcement agencies in terms of building a democratic state with an active civil society is emphasised. Public control is an instrument of public assessment of the implementation of public tasks by law enforcement agencies. Control over the activities of the National Police in Ukraine allows to regulate the relationship between the government and the community, which is an integral feature of all democratic states. The specificity of public control, in comparison with other types of control, is the subject-object sphere, which is manifested in the public's control. In the process of public control, the implementation of social tasks directly related to the protection and realisation of the rights and freedoms of citizens, as well as satisfaction and harmonisation of social needs and interests of the population is monitored. The main forms and subjects of public control are defined. Public control over the activities of the National Police can be carried out by individual and collective, organized and unorganized subjects whose activity profile is general or law enforcement oriented. According to their legal status, the subjects of public control over police activities can be natural or legal entities of private law and associations of citizens without the status of a legal entity. Important subjects of public control over the activities of the National Police in Ukraine are mass media, public councils and public organizations. It has been concluded that public control allows to improve the quality of police activities and to influence the implementation of changes in the activities of the National Police in Ukraine, which is especially important during a full-scale war.